Avifauna of the El Pambilar Wildlife Refuge in Ecuador - Edith Montalvo; Javier Pianchiche; Alex Garofalo; José Bonilla; Freddy Gallo-Viracocha; Luis Montalvo (Biodiversity Data Journal)
The Pambilar Wildlife Refuge (RVSP) is a well-preserved forest on the northern coast of Ecuador and an important refuge for birds, particularly for species with distributions restricted to the Chocó. Data were collected over 83 days from 7 October 2013 to 28 August 2019. This dataset contains 3,638 records, representing 116 orders, 39 families, 120 genera and 158 species.This dataset represents the first article published on the avifauna of the El Pambilar Wildlife Refuge (RVSP) including information collected from 2013 to 2019. It includes taxonomic data collected over several years, as well as detailed information on the location, sampling effort and dates of the surveys. All data are available at the Global Biodiversity Information Facility (GBIF).